2014
DOI: 10.1155/2014/871439
|View full text |Cite
|
Sign up to set email alerts
|

NovelKIF6Polymorphism Increases Susceptibility to Type 2 Diabetes Mellitus and Coronary Heart Disease in Han Chinese Men

Abstract: Objectives. The effect of the KIF6 polymorphism Trp719Arg on the risk of T2DM and T2DM with CHD remains unclear. Methods. 946 unrelated subjects of Han Chinese origin were recruited, comprising 346 controls, 312 T2DM, and 288 T2DM + CHD patients. Genotyping was performed by high-resolution melting curve analysis using real-time qPCR. The impact of the variant on T2DM/T2DM + CHD and gene-sex interaction were evaluated by stepwise multiple regression analysis. Results. The frequencies of the Trp719 allele in T2D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
1
9
0
1
Order By: Relevance
“…Besides the HMG-CoA polymorphism, we also observed a correlation between KIF6 rs20455 and HDL level; in particular, homozygous carriers of the G-minor allele showed higher serum HDL-C. The rs20455 variant is a non-synonymous polymorphism, leading to the replacement of a non-polar Trp with a basic Arg at codon 719, widely screened in relation to cardiovascular events, serum lipids and statin treatment outcome in various populations, with contrasting results [ 20 , 21 , 42 , 43 , 44 , 45 , 46 , 47 ]. To the best of our knowledge, our study is the first reporting an association with the KIF6 719Arg variant and HDL-C, while no apparent difference or opposite results were observed in previous studies [ 20 , 21 , 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the HMG-CoA polymorphism, we also observed a correlation between KIF6 rs20455 and HDL level; in particular, homozygous carriers of the G-minor allele showed higher serum HDL-C. The rs20455 variant is a non-synonymous polymorphism, leading to the replacement of a non-polar Trp with a basic Arg at codon 719, widely screened in relation to cardiovascular events, serum lipids and statin treatment outcome in various populations, with contrasting results [ 20 , 21 , 42 , 43 , 44 , 45 , 46 , 47 ]. To the best of our knowledge, our study is the first reporting an association with the KIF6 719Arg variant and HDL-C, while no apparent difference or opposite results were observed in previous studies [ 20 , 21 , 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to its significant association with lipid levels, the response to lipid-lowering medication, and non-fatal MI, the 719Arg might also be linked to CHD development in T2D individuals. Wu et al, (2014) identified that the same variant was associated with a 5-fold higher CHD risk in T2D in a dominant model of 719Trp/Arg + Arg/Arg compared to the 719Trp/Trp genotype (OR: 5.21) [ 17 ]. In line with previous reports, higher serum TG and lower serum HDL were noted in the T2D and T2D + CHD carriers of the 719Arg risk allele [ 17 ].…”
Section: Genetic Factors Associated With Chd Risk In T2d Asian Populationsmentioning
confidence: 99%
“…It is one of the leading causes of morbidity and mortality, resulting in more than 8 million annual deaths worldwide [ 12 ]. On top of well-known non-genetic risk factors such as age, gender, family history of CHD, hypertension, dyslipidemia, overweight/obesity and sedentary lifestyle, cigarette smoking, as well as alcohol intake [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], various genetic factors have been linked to the disease. Alleles of genetic variants or single nucleotide polymorphisms (SNPs) may influence gene and protein expression by modulating the promoter activity, DNA methylation status, post-transcriptional mRNA processing, mRNA stability, or promoting the interaction with micro-RNA for RNA interference.…”
Section: Introductionmentioning
confidence: 99%
“… 41 Sex analysis revealed that higher TGs and lower HDL-C increased the risk of T2DM and T2DM + CHD. 47 The results of the matched case-control study from Japan demonstrated that HDL-C was significantly related to CHD and that non-HDL-C was the most effective predictor of the development of CHD in T2DM patients. 48 …”
Section: Discussionmentioning
confidence: 99%